2012
DOI: 10.1002/jhm.1004
|View full text |Cite
|
Sign up to set email alerts
|

Defining and measuring the effort needed for inpatient medicine work

Abstract: BACKGROUND:Current metrics for assessing physician workload are inadequate. Understanding the effort associated with work tasks could make workload assessments more robust.OBJECTIVE:To assess the physical, mental, and psychological effort needed for the tasks performed by internal medicine doctors while admitting a patient to the hospital.DESIGN:Cross‐sectional survey.SETTING:A single Midwest academic institution.SUBJECTS:Internal medicine housestaff, hospitalists, and nonhospitalist internal medicine faculty.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The RA operated a data-logging laptop computer that ran custom data collection software, which has been refined over the last 14 years and has been demonstrated to be effective at measuring the effects of a variety of performance shaping factors. [10][11][12][13] This software contained all possible tasks performed by the intern, based on a pilot study 14 (task list available online). The observer recorded each of the intern's tasks by clicking on the appropriate task button on the computer display ( Fig.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…The RA operated a data-logging laptop computer that ran custom data collection software, which has been refined over the last 14 years and has been demonstrated to be effective at measuring the effects of a variety of performance shaping factors. [10][11][12][13] This software contained all possible tasks performed by the intern, based on a pilot study 14 (task list available online). The observer recorded each of the intern's tasks by clicking on the appropriate task button on the computer display ( Fig.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…This suggests that increased burnout on specific rotations is likely related to other factors such as the density of work, patient load, and acuity of illness, consistent with prior literature. 10,12,16 Variable amounts of ancillary support and logistical challenges specific to various practice locations also may contribute to burnout.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we decomposed and further classified all work activities physicians performed during outpatient encounters into the two large groups based on a time-motion task analysis on 32 Chinese physicians from public tertiary hospitals: physician-patient communication work tasks (comprising six categories of work tasks) characterized by direct patient interaction, and non-physician-patient communication work tasks (comprising seven categories of work tasks) characterized by paperwork ( 27 ). Research indicated that gaining insight into the effort associated with work tasks could make workload assessments more robust, since task analysis might facilitate workload measurement by the individual work components or subtasks to be measured ( 28 ). The definition of the detailed work tasks performed by physicians in outpatient practice can provide a solid foundation for the present study to further seek to comprehensively assess physician workload with the consideration of the content and nature of work tasks tethered to outpatient practice.…”
Section: Introductionmentioning
confidence: 99%